The Aluffi algebra of an ideal - Nasrollah Nejad, Abbas (2010)
Nasrollah Nejad, Abbas; Simis, Aron. The Aluffi algebra of an ideal. 2010. Tese (Doutorado). Programa de Pós-Graduação em Matemática, Universidade Federal de Pernambuco, Recife, 2010.